2017
DOI: 10.1021/acs.biochem.6b01048
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the Binding Kinetics for the Inhibition of the Burkholderia pseudomallei FabI1 Enoyl-ACP Reductase

Abstract: There is growing awareness of the link between drug-target residence time and in vivo drug activity, and there are increasing efforts to determine the molecular factors that control the lifetime of a drug-target complex. Rational alterations in drug-target residence time require knowledge of both the ground and transition states on the inhibition reaction coordinate, and we have determined the structure-kinetic relationship for 22 ethyl or hexyl substituted diphenyl ethers that are slow-binding inhibitors of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…There are many hydrophobic interactions between triclosan and ENR, but only one possible hydrogen bond is present between the 2‐OH group and tyrosine in the Tyr–Lys pair (i.e., Tyr156–Lys163 in Ec FabI and Tyr157–Lys164 in Sa FabI). In fact, this triclosan‐binding site also serves as other inhibitors [9,27,30–32] and coincides with that of a fatty acid substrate in the structure of FabI of M . tuberculosis (PDB id http://www.rcsb.org/pdb/search/structidSearch.do?structureId=1BVR) [28].…”
Section: Resultsmentioning
confidence: 87%
“…There are many hydrophobic interactions between triclosan and ENR, but only one possible hydrogen bond is present between the 2‐OH group and tyrosine in the Tyr–Lys pair (i.e., Tyr156–Lys163 in Ec FabI and Tyr157–Lys164 in Sa FabI). In fact, this triclosan‐binding site also serves as other inhibitors [9,27,30–32] and coincides with that of a fatty acid substrate in the structure of FabI of M . tuberculosis (PDB id http://www.rcsb.org/pdb/search/structidSearch.do?structureId=1BVR) [28].…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, studies with FabI1 Enoyl-ACP Reductase from Burkholderia pseudomallei have shown that αhelix 6 (the so-called substrate binding-loop, represented by the residues Thr194-Gly199, original numbering from BpFabI1), becomes ordered and closed upon ligand binding. [31] In our EcFabI studies, also a flexible loop (comprised by the residues 191 to 205) covers the active site, as mentioned previously, which contains the key residues related to the inhibitor interaction ( Figure 4A), and were kept ordered during most of the simulations with the exception of compound 24 and the neutral forms of compound 41 and TCL ( Figure 4C-H and Supporting information, Figure 4, showing the comparison between the ligand-free and bound systems' RMSD values).…”
Section: On the Comparison Between Csm And MD Resultsmentioning
confidence: 99%
“…Kinetic and structural studies with the compound 41 related the effect of 5-ethyl substituents with the increases in the residence time, which presumably is related to the stabilization of the ground state's protein conformation. [31] Additionally, three-dimensional structures of BpFabI1 co-crystallised with different TCL analogues showed that Phe203 rotates toward Leu207 displacing Ala197 (equivalent to the Ala196 of EcFabI), upon ligand binding, which creates a hydrophobic pocket that accommodates the 5-ethyl group. Complementarily, in EcFabI, the Ile200 and Phe203 amino-acids compose the beginning of the short loop (near the α-helix-8) and end, which surrounds the ethyl moiety in our simulations.…”
Section: On the Comparison Between Csm And MD Resultsmentioning
confidence: 99%
See 2 more Smart Citations